"Don't bully! We are all different": Pedagogical potential of early critical literacy with bullying-themes. (December 2022) - Wee, Su-Jeong; Kim, So Jung; Kim, Jinhee
In spite of the increased attention that has been given to early critical literacy practices, there remains a limited amount of scholarship dedicated to exploring how critical literacy may be implemented in early childhood classrooms to prevent bullying. As such, the purpose of this article is to examine the pedagogical potential of early critical literacy with bullying-themes, for educating young children on anti-bullying. Using a qualitative study approach, this study was conducted in a classroom of twenty 5-year-old children in a metropolitan city in South Korea. The central focus of this study was dedicated to examining how children's understanding of bullying toward their peers of different racial/ethnic backgrounds and special needs change through a series of critical literacy activities, including reading, discussion, and follow-up role-playing and writing activities. Findings suggest that critical literacy activities on bullying have the potential to aid in creating anti-bullying environments in which young children critically examine bullying issues from multiple perspectives and actively generate their own understanding of bullying.